EVALUASI KINERJA RUAS JALAN KAWASAN TAMAN BUKIT GELANGGANG KOTA DUMAI MENGGUNAKAN APLIKASI VISSIM - Guruh Sawita Gara; Muhammad Idham (Jurnal TeKLA, 2023)
The Dumai city area began to develop along with the rapid population growth with a total of more than 350 thousand people, the Dumai city government began to think about making a place of worship as well as a tourist nuance as a community recreation center along with a city green park adjacent to the hill arena park, the location of the hill arena park which is in an urban area will have a negative impact on the surrounding traffic conditions if it is not handled properly. The method used in evaluating the performance of roads due to traffic and surrounding development is using PKJI 2014 and the Vissim Student Version Software application. The results of the analysis using PKJI 2014 obtained a capacity value of 7869 Skr/Hour for Jendral Sudirman Road and 5988 Skr/Hour for HR. Soebrantas Road and 6925 Skr/hour for Jalan Raya Bukit Datuk. Of the three roads, the highest degree of saturation is on the road Raya Bukit Datuk obtained a saturation degree value of the existing conditions of 0,48. This explains that judging from the service level values being analyzed, the flow does not yet require repairs, either widening or other improvements.